Technology and work: New sociological approaches? - A. Branda\~o Moniz; Bettina-Johanna Krings; Philipp Frey (TATuP-Zeitschrift für Technikfolgenabschätzung in Theorie und Praxis, 2018)
From 15-21 July 2018, the World Congress of Sociology, organized by the International Sociological Association (ISA), took place in Toronto, Canada. Here, TA research continued to feature prominently at ISA, this time focusing on conceptual approaches to the relation of technology and work. The session on "Technology and Work: New Sociological Approaches?" provided perspectives from several countries and regions as well as from different disciplinary approaches.
Keywords: O33; O35; B59; 330; sociology; work; technology